Effect of Word Familiarity on Speech Discrimination Scores - Asha Devaraj (Journal of All India Institute of Speech and Hearing, 1970)
One of  the basic  requirements of  any organism is the  need to communicate. Speech  has been the most commonly used mode of communication among human beings